التعددية في العمارة العربية المعاصرة ، صراع بين الانتماء والنزعات التغيرية - نصرة, ميرنا (Latakia University Journal -Engineering Sciences Series, 2016)
Modern Arabic architecture has been facing important challenges imposed in many fields by changes occurring internationally and in the West, especially in terms of architecture. The effect of these changes on the visual appearance of the city has been clearly evident, with everything this entails in terms of formation and architectural samples. This was due to a group of internal and external effects which contributed to accelerating the spread of intellectual theoretical movements and new architectural philosophies which differed in how they responded to local data.This really problematic trend in modern Arabic architecture became apparent and manifested itself by achieving balance and integration between originality and tradition on the one hand, and modernism and contemporariness on the other. The number of frames available to the Arabic architect became more numerous, to include rejection, advocacy and reformation, and this was reflected in the architectural formations which became multiple and were characterized by pluralism. This led to the loss of their local identity and to a contradiction between their visual and formative modes. A number of Arab architects became aware of this problem at the end of the 20th century, so they analyzed its causes and its transformative mechanism. Attempts were started to find logical and rational solutions to guarantee harmony between technical and scientific development on the one hand, and a sense of belonging to the place on the other. تعرضت العمارة العربية المعاصرة إلى تحديات هامة, فرضتها طبيعة التغيرات العالمية الغربية في كافة المجالات وخاصة المعماري منها, فظهر تأثيرها بشكل واضح في تغيير الصورة البصرية للمدينة, بما تحتويه من تكوينات ونماذج معمارية ,وذلك بفعل مجموعة من المؤثرات الخارجية والداخلية التي ساهمت في تسريع دخول اتجاهات نظرية فكرية وفلسفات معمارية جديدة, اختلفت في استجابتها للمعطيات المحلية. ظهرت الإشكالية الحقيقية للعمارة العربية المعاصرة وتجلت في تحقيق التوازن و التكامل بين الأصالة و التقليدية من جهة, والحداثة والمعاصرة من جهة أخرى, فتعددت الأطر الفكرية للمعمار العربي بين رفض و تأييد و إصلاح, وانعكس ذلك على التكوينات المعمارية, فاتسمت أيضاً بالتعددية مما أدى إلى ضياع هويتها المحلية و تناقض صيغها التكوينية والبصرية .بدأ الوعي لهذه الإشكالية بين بعض المعماريين العرب في نهاية القرن العشرين , فعمدوا إلى تحليل مسبباتها وآلية تحولها, وبدأت المحاولات لإيجاد حلول منطقية وعقلانية تؤمن التوافق بين التقنية والتطور العلمي من جهة, والانتماء للمكان من جهة أخرى .